Effects of daylength and soil humidity on the flowering of coffee coffea arabica l. in colombia. (2011)
Coffee flowering data were analyzed in order to explore the effect of two environmental variables that have been considered relevant for this process. Pre-anthesis stage flowers were counted in coffee leaf-rust resistant crops at eight experimental stations (between 2°N and 11°N). Likewise, climatic data were taken to generate a humidity soil index, whereas day longitude data were taken from the Smithsonian Meteorological Tables. Flowering data were compared with a sunshine index to understand better the effect of light on flowering. This data (flowering, soil humidity index and day length) were expressed in a monthly scale and analyzed using linear regression and cross-correlation functions. The main results show that there is a significant correlation between short days and high flowerings, whereas soil humidity (dry months) are related to the phenomenon, but to a lesser extent.